“It's a Balancing Act!”: Exploring School/Work/Family Interface Issues Among Bilingual, Rural Nebraska, Paraprofessional Educators. - Dalla, Rochelle L.; MolikGupta, Pallabi; Lopez, William E. (Family Relations, 2006)
Nebraska's rural school districts have a rapidly growing Spanish-speaking student body and few qualified instructors to meet their educational needs. This investigation examined factors that promote and challenge the ability of rural Nebraska paraprofessional educators to complete an online B.S. program in elementary education, with a K-12 English as a second language endorsement. Interviews focused on the interface between school, work, and family, with special attention on family system change and adaptation. Twenty-six bilingual paraprofessional educators enrolled (or formerly enrolled) in the education program were interviewed. Twenty were first- (n = 15) or second-generation (n = 5) immigrant Latino/as. Influences of program involvement on the marital and parent-child relationships are discussed, as are implications for future work with unique populations. Reprinted by permission of the publisher.